Tradisi “Sedekah Bumi” dalam Prespektif Perlindungan dan Pengelolaan Lingkungan Hidup - Yusuf Eko Nahuddin; Khotbatul Laila; Achmad Reza Wahyudi (Journal on Education, 2023)
This study aims to determine the meaning of the almsgiving earth tradition in people's lives and the correlation of the meanings of the almsround earth tradition in the perspective of the value of environmental protection and management. This research method uses normative legal research with a statutory and conceptual approach. As for the results of the research that the almsgiving earth tradition in people's lives in principle has values including the values ​​of hablum minallah, hablum minannas and hablumminal alam, while the meaning of the alms earth tradition has a correlation with the values ​​or principles of environmental protection and management, namely with some values ​​or principles include; the value of sustainability and sustainability, the value of harmony and balance, the value of integration, the value of utilization, the value of prudence, the value of justice, the value of participatory and the value of local wisdom, from this correlation it is hoped that the values of almsgiving can encourage the birth of habits from human awareness as khalifatul fil ardhi to position the environment as a subject that has fundamental rights (human rights as nature/environment) as well as human positions to be protected so that in the end between the environment and humans protect and love one another.